Supplement to Frege's Theorem and Foundations for Arithmetic

Proof of the Principle of Extensionality from Basic Law V

[Note: We use εF to denote the extension of the concept F.]

Assume Extension(x) and Extension(y). Then ∃F(x = εF) and ∃G(y = εG). Let P,Q be arbitrary such concepts; i.e., suppose x = εP and y = εQ.

Now to complete the proof, assume ∀z(zxzy). It then follows that ∀z(z ∈ εPz ∈ εQ). So, by the Law of Extensions and the principles of predicate logic, we may convert both conditions in the universalized biconditional to establish that ∀z(PzQz). So by Basic Law V, εP = εQ. So x = y.

Copyright © 2013 by
Edward N. Zalta <>

Open access to the SEP is made possible by a world-wide funding initiative.
The Encyclopedia Now Needs Your Support
Please Read How You Can Help Keep the Encyclopedia Free